Research perspectives on social media influencers and their followers - Watkins, Brandi (Lexington Books, 2021)
"This book analyzes social media influencers and their relationship with their online followers. Each chapter represents a unique theoretical and methodological approach to examining the importance of this relationship from a variety of perspectives and contexts"--Provided by publisher.